Next-generation sequencing and histological response assessment in peritoneal metastasis from pancreatic cancer treated with PIPAC - Nielsen, Malene (J Clin Pathol, 2021)
BACKGROUND: Peritoneal metastasis from pancreatic cancer (PM-PC) may be treated with repeated pressurised intraperitoneal aerosol chemotherapy (PIPAC). Utility of next-generation sequencing (NGS) to detect cancer-related mutations in peritoneal quadrant biopsies (QBs) and peritoneal fluid (PF) after systemic and PIPAC treatment has not been evaluated. Around 90% of pancreatic cancers (PCs) harbour a KRAS mutation, making PC ideal for the evaluation of this aspect. AIMS: Evaluation of PM-PC in terms of (1) histological response to PIPAC using Peritoneal Regression Grading Score (PRGS), (2) clinical characteristics and (3) frequency of mutations in QBs and PF before and after PIPAC. METHODS: Peritoneal QBs and PF were obtained prior to each PIPAC. NGS for 22 cancer-related genes was performed on primary tumours, QBs and PFs. Response was assessed by the four-tiered PRGS. RESULTS: Sixteen patients treated with a median of three PIPAC procedures were included. The mean PRGS was reduced from 1.91 to 1.58 (p=0.02). Fifty-seven specimens (13 primary tumours, 2 metastatic lymph nodes, 16 PFs and 26 QB sets) were analysed with NGS. KRAS mutation was found in 14/16 patients (87.50%) and in QBs, primary tumours and PF in 8/12 (66.67%), 8/13 (61.53%) and 6/9 (66.67%). The median overall survival was 9.9 months (SE 1.5, 95% CI 4.9 to 13.9). CONCLUSION: PIPAC induces histological response in the majority of patients with PM-PC. KRAS mutation can be found in PM-PC after PIPAC at a frequency similar to the primaries. NGS may be used to detect predictive mutations in PM-PC of various origins, also when only post-PIPAC QBs or PFs are available.